Просто жить - Невская Ирина (75 Победа! 1945-2020, 2020)
Экземпляры: Камская библиотека (20220629) / Инвентарный номер: 15691 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Н 40 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6